2021
DOI: 10.7759/cureus.18808
|View full text |Cite
|
Sign up to set email alerts
|

Regional Anesthesia in Cardiac Surgery: A Review of the Literature

Abstract: With our population getting older and sicker, we are witnessing a steady increase in the volume of cardiothoracic procedures performed. As the role of anesthesiologists continues to shift towards being perioperative physicians, it is crucial to tailor the anesthetic to manage the surgical pain in both intraoperative and postoperative periods. In cardiac surgery, poorly controlled surgical pain can lead to opioid-induced hyperalgesia as well as chronic pain syndrome. As current practice encourages early extubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…But the intraoperative anticoagulation is a concern expressed by many anesthesiologists. [ 33 ] Several chest wall blocks have been described in the last two decades and have been successfully used in patients undergoing cardiac surgeries. These blocks are pectoral nerve blocks (PECS 1 and PECS 2), serratus anterior plane block, parasternal blocks like transversus thoracis muscle plane block, and the ESPB.…”
Section: Discussionmentioning
confidence: 99%
“…But the intraoperative anticoagulation is a concern expressed by many anesthesiologists. [ 33 ] Several chest wall blocks have been described in the last two decades and have been successfully used in patients undergoing cardiac surgeries. These blocks are pectoral nerve blocks (PECS 1 and PECS 2), serratus anterior plane block, parasternal blocks like transversus thoracis muscle plane block, and the ESPB.…”
Section: Discussionmentioning
confidence: 99%
“…Neuraxial anesthesia may also worsen hypotension in patients with normal or low blood pressure. Additionally, there is a concern for increased risks of bleeding and hematoma formation with neuraxial anesthesia in the setting of high-dose intraoperative heparin required during CPB [9]. In contrast to neuraxial anesthesia, general anesthesia provides a secure airway in a patient at high risk of aspiration (being a full-term pregnant patient undergoing emergency surgery) who can quickly become hemodynamically unstable.…”
Section: Discussionmentioning
confidence: 99%
“…Data on regional analgesia are extremely limited in the context of cardiac surgery, as they come from small sample sizes with high heterogeneity in techniques and the measurement of outcomes. Nevertheless, the available evidence indicates that loco-regional analgesia could facilitate enhanced recovery pathways [15,20,26,28,29,45,47]. The recent joint consensus from the ERAS Cardiac Society, the ERAS International Society and the Society of Thoracic Surgeons (STS) recommended chest wall regional analgesia as "an effective component of a multimodal approach to perioperative pain management" [29] and suggested that further research is required to establish delivery methods and the efficacy of locoregional pain control in cardiac surgery.…”
Section: Analgesia Anaesthesia and Early Extubationmentioning
confidence: 99%